Kepemimpinan Lokal dan Ketahanan Ekonomi di Era Pandemi: Studi Kasus Desa Janti, Kecamatan Waru, Kabupaten Sidoarjo - Cut Putri Rohmayani; Laili Bariroh (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The purpose of this study was to determine the efforts of the Village Head to utilize social capital, political and cultural capital of the community in improving the economy and to analyze the economic resilience of rural communities in the Covid19 pandemic era. To be able to answer the formulation of the problem, the author uses a descriptive qualitative method with a case study approach. Data collection techniques are in the form of observation, interviews, and documentation. The theory used in this study is Randall G. Holcombe's Political Entrepreneurship theory. The results of the study, the village head utilizes social, political, economic and cultural capital through an e-commerce service in the form of e-market and pitulungan-e in collaboration with BUMDes and the community to improve the community in the creative economy. The village head of Janti provides technology education by socializing e-market e-commerce and e-pitulungan for the community. The head of the Janti village also applies transparency to BUMDes to remove dynastic politics in Janti village. The economic resilience in Janti village during the pandemic is illustrated by the existence of e-market e-commerce. In addition, the daily income of the community reaches IDR20,000 to IDR50,000 from sales of e-market e-commerce. There is a profit which is distributed 50% to the community by the BUMDes civil welfare. The community becomes social and creative in the economic and does not experience the impact of a large economic downturn during the pandemic